KAUMAN: A Moslem Neighborhood of Yogyakarta - Sjafri Sairin (Humaniora, 1998)
This brief paper is meant to discuss the social and economic life of a united community who lives in the kampong of Kauman.It is a residence which is situated in the heart of Yogyakarta toward the west of Northern Aloon-aloon, to be precise. This particular kampong is interesting to discuss for some reasons. First, it is the one that none of us could separate fromthe history of Yogyakarta. More importantly, it is dennitely a part of the sultanate bureaucratic system of the kraton. Beyond doubt, the kampong reflects, too, the dimensions of yesterday, today and tomorrow. Second, since Yogyakarta was founded, Kauman has become a Javanese community which, according toGeertz (1960) is caned a Santri society. They profess Islam and obediently perform their religious obligations, which distinguishes themselves from the communities in the other kampongs in Yogyakarta. Third , the Muhammadiyah organization was founded in this kampong by K.H . Dahlan in 1912.lt is indeed an organization which has been considered as the Islamic reformer in Indonesia. People from all over the country now accept his organization as the most influential, and so do people from the neighboring countries especially Southeast Asia . This organization has thousands of schools, hundreds of hospitals and clinics, orphanages and old folk's homes, in addition to hundreds of universities and Institutions of higher education, which are available in every corner of the country.